Notch Fatigue Damage Evolution Mechanism of TC21 Alloy with Multilevel Lamellar Microstructures - Xiaosong Zhou; Xiang Li; Chaowen Huang; Quan Wu; Fei Zhao (Metals)
This study aims to explore the effect of microstructural parameters on the notch fatigue damage behavior of the TC21 alloy. Different levels of lamellar microstructures were achieved through distinct aging temperatures of 550 °C, 600 °C, and 650 °C. The findings reveal that increasing aging temperature primarily contributes to the augmentation of α colony (αc) thickness, grain boundaries α phase (GBα) thickness, and α fine (αfine) size alongside a reduction in α lath (αlath) thickness and αfine content. The notch alters stress distribution and relaxation effects at the root, enhancing notched tensile strength while weakening plasticity. Moreover, the increased thickness of GBα emerges as a critical factor leading to the increase area of intergranular cleavage fracture. It is noteworthy that more thickness αlath and smaller αfine facilitate deformation coordination and enhance dislocation accumulation at the interface, leading to a higher propensity for micro-voids and micro-cracks to propagate along the interface. Conversely, at elevated aging temperatures, thinner αlath and larger αfine are more susceptible to fracture, resulting in the liberation of dislocations at the interface. The reduction in αlath thickness is crucial for triggering the initiation of multi-system dislocations at the interface, which promotes the development of persistent slip bands (PSBs) and dislocation nets within αlath. This phenomenon induces inhomogeneous plastic deformation and localized hardening, fostering the formation of micro-voids and micro-cracks.